Drift and Its Mediation in Terrestrial Orbits - Daquin, Jérôme; Gkolias, Ioannis; Rosengren, Aaron J. (Frontiers in Applied Mathematics and Statistics, 2018)
The slow deformation of terrestrial orbits in the medium range, subject to lunisolar resonances, is well approximated by a family of Hamiltonian flow with $2.5$ degree-of-freedom. The action variables of the system may experience chaotic variations and large drift that we may quantify. Using variational chaos indicators, we compute high-resolution portraits of the action space. Such refined meshes allow to reveal the existence of tori and structures filling chaotic regions. Our elaborate computations allow us to isolate precise initial conditions near specific zones of interest and study their asymptotic behaviour in time. Borrowing classical techniques of phase-space visualisation, we highlight how the drift is mediated by the complement of the numerically detected KAM tori.